L’enfant pauvre et la naissance de la photographie sociale aux États-Unis au XIXe siècle - Anne LESME (E-REA, 2010)
At the end of the 19th century, Jacob Riis, journalist and photographer, brought to light the appalling conditions of the slums in New York; it was the beginning of the social documentary photography in the United States. The representation of destitute children was to become central in this genre. His photographs, used during stereopticon slides projections and published in books and articles, contributed to a change of mentality. However influenced by a middle-class vision of the Lower East Side’s children, Jacob Riis’s photographs contributed to bring a new perception of poverty in line with a child who was from that time perceived as innocent by a large part of society. This particular use of photography as a convincing and reliable medium added to the text initiated a new means of communication used by the reformers to move and provoke reactions from a middle and upper-class public.